ANALISIS PENDAPATAN USAHATANI DENGAN POLA TANAM PADI-PADI-JAGUNG DAN PADI-PADI-SEMANGKA DI KELURAHAN TEJOSARI KECAMATAN METRO TIMUR KOTA METRO - Selvia Septa Kharisma; Sudarma Widjaya; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The aims of this study are to determine the profit, income of farmer households and to analyze the difference of return, income, and costs between paddy-paddy-corn and paddy-paddy-watermelon crop systems in Tejosari, East Metro subdistrict, Metro City. The method used in this research is a survey method. Data were collected in March-April 2018. The study uses a sensus sampling method with the number of respondents consisted of 30 farmers practicing the paddy-paddy-corn crop system and 10 farmers of the paddy-paddy-watermelon crop system. The results of this study indicated that the more beneficial crop system is the paddy-paddy-watermelon crop system. The income of farmer households from the agricultural sector (on farm and off farm) still provides the largest contribution and there is differencein return, income, and costs between the system of paddy-paddy-corn and pady-paddy-watermelon crop systemKey words: crop system, household income, profit